Student Engagement in Academic Reading Viewed through Predicting, Previewing, and Anticipating Processes - Magvirah Octasary; Nahdawati; Hujaefa Hi. Muhammad (Universitas Islam Negeri Palopo, 2026)
Academic reading is a fundamental component of higher education, particularly for English as a Foreign Language (EFL) students who are frequently required to engage with complex academic texts. However, many students experience difficulties in understanding such texts due to limited use of effective reading strategies. This study aims to examine students’ engagement in academic reading through the implementation of three pre-reading and during-reading strategies: previewing, predicting, and anticipating. The research employed a descriptive approach involving ten university students as participants. Two instruments were used to collect data, reading comprehension tasks and a questionnaire. The reading tasks were designed to assess how students applied previewing, predicting, and anticipating strategies while interacting with an academic text, whereas the questionnaire measured students’ perceptions of the usefulness of these strategies using a Likert-scale format. The findings indicate that previewing helped most students identify the general topic and activate relevant prior knowledge before reading the text. In the prediction task, eight out of ten students were able to generate reasonable expectations about the content based on textual clues such as the title and accompanying images. Furthermore, the majority of participants successfully anticipated possible outcomes or conclusions after completing the reading activity, suggesting an increased level of engagement with the text. The questionnaire results also revealed generally positive perceptions toward the strategies, with most mean scores exceeding 3.5, indicating that students considered previewing, predicting, and anticipating helpful in supporting their comprehension of academic texts. Nevertheless, some students still encountered difficulties in making precise predictions and consistently applying these strategies throughout the reading process. Overall, the study suggests that integrating structured reading strategies such as previewing, predicting, and anticipating into academic reading instruction can promote more strategic engagement and improve students’ comprehension of academic texts in EFL contexts.